Enhancing the performance of video encryption used for security and privacy protection in secure multimedia transfer - O. Khorsheed, Khattab; G. Abood, Omar; K. Guirguis, Shawkat (International Journal of Engineering and Technology, 2019)
It is taken for granted that the techy core transfer has showed an upward indicator recently. Data exchanges could be a mutual subject over unsecure network, the matter that made the multi-media security an inevitable and crucial issue. Applications that require image and video processing became extremely popular in many fields, e.g. Medical imaging, manufacturing, and security systems. Real time image and video processing is considered a vital matter, since it requires high computations for a huge a video data and complicated process in return. Thus, to guarantee the confidentiality via the vulnerable network, along transmission, a video encoding is considered a priority. As a matter of fact, valid algorithms are subject for violating. However, our academic research tackles an up-to-date system for real time video encrypting by using pixel encryption. Pixel encryption thesis relays on shuffling and manipulating pixel values. According to unscrambled order generated, the position of pixel values is changed. All in all, decrypting to edit the initial video would be hold by rearranging the pixel values first, then manipulating them reversely for a recipient side.Â Â
Keywords: Key Exchange; Pixel Shuffling; RGB Pixel Displacement; Video Decryption; Video Encryption.